Assess Different Forms of Domestic Violence During Pregnancy and Maternal Outcome - Amel Dawod Kamal; Amen Mustafa; Ahmed Ramadan; Mohamed Rashad; Bedor Fathey; Mustafa Mohammed; Livana PH (GLOBAL HEALTH SCIENCE GROUP, 2020)
Domestic violence is Violence during pregnancy as violence or threat of physical, sexual or psychological (emotional) violence against pregnant women. The present study aims to:- Assess different forms of violence that women are exposed to by their partners during pregnancy Explore consequences of domestic violence on pregnant women out come. A descriptive exploratory research design was adopted in this study to achieve the stated aim. Postpartum units were selected from at El-manial maternity hospital, this hospital is a university-affiliated hospital which providing free health care service topostpartum women and their newborn. Structured interviewing questionnaire, domestic violence assessment tool, and maternal pregnancy outcome tool. Indicated that age of woman ranged from 15-45 years with mean 31.65 +/- 6.79. 42% of sample living in urban areas, while 58% living in rural areas. Percentage of domestic violence according to total domestic violence scale 82% suffer from different type of domestic violence, regarding the maternal outcome20% of cases have bleeding during delivery , 24% exposed to premature rapture of membrane, and 30% exposed to menstrual problems. Women are exposed to different forms of domestic violence during pregnancy. These forms of violence have an impact on the pregnancy outcomes such as abortions, bleeding during delivery, premature rapture of membrane, and menstrual problems others.